The HARP domain dictates the annealing helicase activity of HARP/SMARCAL1 - Ghosal, Gargi (Nature Publishing Group, 2011)
Mutations in HepA-related protein (HARP, or SMARCAL1) cause Schimke immunoosseous dysplasia (SIOD). HARP has ATP-dependent annealing helicase activity, which helps to stabilize stalled replication forks and facilitate DNA repair during replication. Here, we show that the conserved tandem HARP (2HP) domain dictates this annealing helicase activity. Furthermore, chimeric proteins generated by fusing the 2HP domain of HARP with the SNF2 domain of BRG1 or HELLS show annealing helicase activity in vitro and, when targeted to replication forks, mimic the functions of HARP in vivo. We propose that the HARP domain endows HARP with this ATP-driven annealing helicase activity.